Two-Dimensional Speckle Tracking Echocardiography for Early Detection of Myocardial Damage in Young Patients with Fabry Disease - Saccheri, María C. (2013)
Fabry disease (FD) is characterized by left ventricular hypertrophy (LVH). Conventional echocardiography is not sensitive enough to perform the preclinical diagnosis To assess whether longitudinal myocardial strain of the left ventricle (LV), using speckle tracking, is useful to detect early myocardial involvement in FD. Forty‐four patients with FD who were diagnosed with genetic testing were prospectively included and were compared to a sex‐matched control group. They were divided into three groups: 22 with LVH (Group I), 22 without LVH (Group II), and 22 healthy volunteers (Group III). LV longitudinal strain was measured from the apical views. An ANOVA test was used for multiple comparisons for variables with a normal distribution, and a Kruskal–Wallis test was used for variables with non‐Gaussian distribution. Longitudinal LV strain was different in the three groups: it was ≥−15% in at least one segment in all Group I patients, in 50% of patients of Group II and in no patient of Group III. Seventy percent of the segments with abnormal strain in Group II were located in the basal regions (32/46). These findings show that the presence of at least one strain value ≥−15% demonstrates subclinical myocardial dysfunction in patients with preclinical FD. Longitudinal myocardial LV strain measured with speckle tracking is a useful tool to detect early myocardial involvement in young patients with FD. This information allows the detection and treatment of myocardial dysfunction at an early stage, which is of high clinical importance.